2023
DOI: 10.1002/smll.202306806
|View full text |Cite
|
Sign up to set email alerts
|

Nonmetallic‐Bonding Fe–Mn Diatomic Pairs Anchored on Hollow Carbonaceous Nanodisks for High‐Performance Li–S Battery

Tengfei Zhang,
Dengfeng Luo,
Hong Xiao
et al.

Abstract: The issues of polysulfide shuttling and lethargic sulfur redox reaction (SROR) kinetics are the toughest obstacles of lithium–sulfur (Li–S) battery. Herein, integrating the merits of increased density of metal sites and synergistic catalytic effect, a unique single‐atom catalyst (SAC) with nonmetallic‐bonding Fe–Mn diatomic pairs anchored on hollow nitrogen‐doped carbonaceous nanodisk (denoted as FeMnDA@NC) is successfully constructed and well characterized by aberration‐corrected high‐angle annular dark‐field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Electrochemical impedance spectroscopy (EIS) testing for the cell with CC and CC/HEO is tested at 100 to 0.1 kHz, shown in Figure c. The Nyquist plots for the cells can be divided into three parts: in the high-frequency area, the X -axis intercept represents the ohmic resistance, while in the middle- and low-frequency areas, it means the charge transfer resistance ( R ct ). It is clear that the cell with CC/HEO shows smaller R ct (9.2 Ω) compared to the cell with CC (15.4 Ω).…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) testing for the cell with CC and CC/HEO is tested at 100 to 0.1 kHz, shown in Figure c. The Nyquist plots for the cells can be divided into three parts: in the high-frequency area, the X -axis intercept represents the ohmic resistance, while in the middle- and low-frequency areas, it means the charge transfer resistance ( R ct ). It is clear that the cell with CC/HEO shows smaller R ct (9.2 Ω) compared to the cell with CC (15.4 Ω).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the impregnation method is also a common wet‐chemistry strategy for preparing SACs. [ 62–64 ] For example, a homogeneous mixture composed of ZIF‐8 dodecahedral nanocrystals, polyacrylonitrile, and Co(NO 3 ) 2 ⋅6H 2 O was electrostatically spun into nanofibers. Thereafter, the internal components of ZIF‐8 were dissociated and dispersed into the polyacrylonitrile fibers and then carbonized during the high‐temperature thermal process, generating nanovesicles in their initial positions.…”
Section: Synthesis Strategymentioning
confidence: 99%
“…[ 90,191–193 ] To date, the research of dual‐atom catalysts remains in its infancy, the reported literatures so far mainly focused on heterogeneous diatomic catalysts and heteronuclear diatomic catalysts for M–S batteries. [ 88,194,195 ]…”
Section: Regulation Strategies For Janus Metal Atomic‐site Catalystsmentioning
confidence: 99%
“…Although the separator is not an active component within the battery, its role in inuencing crucial aspects such as cost, cycle life, and safety cannot be overstated. [18][19][20][21] The pores in the separator allow lithium ions to conduct between the anode and the cathode during the charge and discharge cycles, facilitating stable electrochemical reactions. Moreover, the separator serves a dual purpose by providing a physical barrier, preventing internal short circuits.…”
Section: Introductionmentioning
confidence: 99%